Pengaruh model pembelajaran berbasis masalah terhadap motivasi belajar dan hasil belajar PPKn - Kurniawan, Mohammad Wahyu; Wuryandani, Wuri (Universitas Negeri Yogyakarta, 2017)
The aims of this study were to analyze: (1) the significance effects of the Problem-Based Learning (PBL) Method on the motivation to learn PPKn, (2) the significance effects of PBL Method on PPKn learning result, (3) the significance effects of PBL on the result and motivation of the students in PPKn learning process, and (4) to find out the effectiveness among PBL Method, the Inquiry and Conventional Learning Method in learning PPKn. This research was quasi experiment by pretest-posttest control group design. The participants were the 10th grade of SMA Negeri 1 Pacet Mojokerto 2016/2017 year academic. The results: (1) there were significance effects of the PBL Method on the motivation to learn PPKn; (2) there were significance effects of PBL Method on PPKn learning result; (3) there were significance effects of Problem-Based Learning on the result and motivation to the students in PPKn learning process; (4) the most effective method of learning PPKn was Problem-Based Learning.